2010
DOI: 10.1111/j.1442-9071.2010.02318.x
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin and soluble CD44 levels in patients with primary open‐angle glaucoma

Abstract: Increased levels of aqueous EPO and sCD44 may be associated with POAG. In addition, EPO and sCD44 may be useful proteins levels in aqueous of POAG patients as a result of glaucoma damage and not a cause. EPO and sCD44 concentrations in aqueous are a possible biomarkers for visual field loss in patients with POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Similarly, increased levels of erythropoietin and soluble CD44 levels were found to be increased in aqueous humor of POAG patients as compared to healthy control, their circulating levels in serum were found to be insignificant. [27]…”
Section: Circulating Biomarkers In Glaucomamentioning
confidence: 99%
“…Similarly, increased levels of erythropoietin and soluble CD44 levels were found to be increased in aqueous humor of POAG patients as compared to healthy control, their circulating levels in serum were found to be insignificant. [27]…”
Section: Circulating Biomarkers In Glaucomamentioning
confidence: 99%
“…Becerra and Amaral (93) hypothesized that identifi cation and separation of the structural determinants within the erythropoietin molecule could elucidate additional ways to minimize side effects associated with local administration of erythropoietin to the eye, an approach that offers advantages over systemic administration. Recently, the role of AH erythropoietin in POAG has been investigated, and the studies have concluded that erythropoietin is a possible biomarker for the disease (61,94,95) .…”
Section: Erythropoietinmentioning
confidence: 99%
“…Other studies suggest that CD44 content in ocular tissue may represent a biomarker for glaucoma (Mokbel et al, 2010). CD44 is transmembrane protein, the principal receptor of the glycosaminoglycan, hyaluronan.…”
Section: Molecular Biomarkers In Glaucomamentioning
confidence: 98%